Totalism - Francis, T (2022)
Totalism in population axiology is the view that one population is better than another if and only if it contains greater total wellbeing. This thesis defends Totalism. I begin, in Chapter 1, by arguing for the principle of Anonymity, according to which any two populations with the same anonymous distribution of wellbeing are equally good. Chapter 2 argues against Prioritarian population axiologies on the basis that they imply the desirability of welfare diffusion: the implausible claim that it can be better for there to be less total wellbeing spread thinly between a larger total number of people. Chapter 3 argues against the popular intuition that adding good lives within a certain range cannot result in a better population. Chapters 4 and 5 provide new evidence for the unavoidability of the Repugnant Conclusion, the controversial implication of Totalism which holds that a smaller population of excellent lives can be worse than a much larger population of mediocre lives (and which is traditionally considered to be a damning objection to Totalism). Chapter 6 argues for a version of Totalism applicable to prudence in fission cases: cases where an individual “splits” into two or more successors, while retaining what matters in survival. Finally, Chapter 7 ties things together and summarises several direct arguments for Totalism. With the exception of Chapter 7, which makes extensive use of results and notation from earlier parts of the thesis, each chapter is entirely self-standing and can be read independently of the others.